2018
DOI: 10.1097/ccm.0000000000003369
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Prognostication in Critically Ill Cirrhotic Patients With Multiorgan Failure in ICUs in Europe and North America: A Multicenter Analysis*

Abstract: The Chronic Liver Failure-Consortium Acute on Chronic Liver Failure demonstrated better discrimination at day 28 and day 90 compared with Acute Physiology and Chronic Health Evaluation II and Child-Turcotte-Pugh. Patients who demonstrated clinical improvement post-ICU admission (e.g., acute on chronic liver failure 3 to 1 or 2) at day 3 had better outcomes than those who did not. In high-risk ICU patients (Chronic Liver Failure-Consortium Acute on Chronic Liver Failure > 70), decisions regarding transition to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 36 publications
(23 reference statements)
1
39
1
1
Order By: Relevance
“…This allows earlier engagement with the ICU and liver transplantation teams, resulting in an increase in the total number of ICU admissions, yet a reduction in mortality (see Table for an assessment of the cost of ACLF to the US economy in comparison with other serious illnesses). In contrast, new thresholds for futility of ongoing ICU care for patients with ACLF have been identified, to permit the release of precious ICU beds with the hope that patients and relatives will not be unduly distressed …”
Section: Impact Of Recognition Of Aclf As a New Syndromementioning
confidence: 99%
See 1 more Smart Citation
“…This allows earlier engagement with the ICU and liver transplantation teams, resulting in an increase in the total number of ICU admissions, yet a reduction in mortality (see Table for an assessment of the cost of ACLF to the US economy in comparison with other serious illnesses). In contrast, new thresholds for futility of ongoing ICU care for patients with ACLF have been identified, to permit the release of precious ICU beds with the hope that patients and relatives will not be unduly distressed …”
Section: Impact Of Recognition Of Aclf As a New Syndromementioning
confidence: 99%
“…In contrast, new thresholds for futility of ongoing ICU care for patients with ACLF have been identified, to permit the release of precious ICU beds with the hope that patients and relatives will not be unduly distressed. [16][17][18]…”
Section: Impact On the Economymentioning
confidence: 99%
“…Requirements for vasopressors and mechanical ventilation were identified as the failures associated with the worst outcomes in some studies 32,48,50 whereas this was not reported in a large recent international study. 40 Liver failure, as defined by a total bilirubin ≥ 12 mg/dl in the CANONIC study, was an independent predictor of a severe lifethreatening course of ACLF, suggesting a central role as a trigger or perpetuating factor of multiorgan failure. 29…”
Section: Key Pointsmentioning
confidence: 84%
“…In this work, CLIF-C ACLF failed to show better perfomance in prediction of 90 days mortality compared to MELD (AUROC 0.68 vs. 0.67, p=0.3). 39,40 Moreover, its daily use seems less convenient than the evaluation of OF number by the CLIF-C OF. Lactate levels were independently associated with short-term mortality in critically ill patients with liver cirrhosis and were shown to significantly improve performance of CLIF-C ACLF.…”
Section: Key Pointsmentioning
confidence: 99%
“…We found similar C‐statistics for the CLIF‐C ACLF score in our cohort, ranging from 0.74 to 0.78. In a separate study of academic Canadian hospitals, the CLIF‐C ACLF score was also used to predict short‐term mortality in 867 ACLF patients admitted to the ICU . This yielded C‐statistics of 0.69 and 0.68 for 28 and 90‐day mortality respectively.…”
Section: Discussionmentioning
confidence: 99%